Immediately Sequential Bilateral Cataract Surgery: the Opinion of Russian Ophthalmologists - D. F. Pokrovsky; I. B. Medvedev (Oftalʹmologiâ, 2022)
Purpose. A study of the attitude of Russian ophthalmologists to Immediately Sequential Bilateral Cataract Surgery (ISBCS).Methods. The study was carried out with the participation of 184 ophthalmologists actively performing cataract surgery, who were presented (in personal contact or via the Internet) a questionnaire developed by the authors, based on three main sections (“I use ISBCS in practice”; “I do not use ISBCS in practice”; “I don’t use, but I did ISBCS before”), which includes in each of the sections a number of clarifying questions and possible answers (“Doesn’t matter”; “Matters”; “Important”; “Very important”). At the same time, the analysis of possible answers was carried out by summing up two possible options — “Negative” opinion (“Not important” + “Matters”) and “Positive opinion” (“Important” + “Very important”). The age of the interviewed ranged from 26 to 58 years (mean age 36.2 ± 1.9 years), the experience of surgical activity in performing cataract phacoemulsification was predominantly (76 %) more than 5 years.Results. The data obtained indicate that 36 respondents (19.8 %) use ISBCS in their practice, 114 (61.8 %) do not use ISBCS; 34 (18.4 %) — do not use, but previously used ISBCS. At the same time, the volume of ISBCS performed on the same day is (for 84 % of respondents) no more than 20 % of the total number of operations performed. As part of the assessment of the main factors, in accordance with which (according to the ophthalmic surgeon), the patient is offered to perform ISBCS by the leader (in terms of the ratio of “positive” and “negative” opinions) is less clinic visits, and less time spent for the patient. The leading reasons for refusal to perform ISBCS by ophthalmic surgeons who do not use this technology are the possible occurrence of endophthalmitis, the risk of errors in IOL calculation, and medical and legal problems.Conclusion. The conducted questioning of domestic ophthalmologists testifies to the low prevalence of ISBCS technology, which is mainly associated with the possible risks of postoperative infectious complications, the lack of a standard protocol for surgical intervention, as well as medical and legal aspects. For the wider use of ISBCS, especially in a difficult epidemiological situation, it is necessary to carry out a set of measures of medical, educational and medical and economic orientation.